Impact of Motivational Program on Student’s Academic Achievement in Higher Education - Abd Rahim, Mohd Azrin; Khalid, Mohd Firdaus; Abdul Hamid, Hafiza (Selangor Humaniora Review, 2021)
This paper aims to present an overview on how motivational program using peer mentoring was applied to a group of University Selangor students who were the recipients of zakat funds to enable them to achieve better performance in their studies. These students mostly come from poor family background with less motivation to excel in their study. A significant number of these students were unable to complete their study due to poor grades in their examination. The objective of this study is to know how far motivational programs may improve their academic achievement. For this purpose, observations on the pre- and post-examination result for these control group models were used. We focused on the two consecutive semesters, April and November 2019. The groups consisted of 114 students who were invited in four separate motivational programs to give them the opportunity to gain motivational input and simultaneously build team spirit among them. Consequently, it was found that the motivation of the students in the experimental group increased based on the improvement of their examination result. However, there might be several factors that also contribute to the student’s motivation. Limitations of this study are the small sample size and the short period of time in which students were asked to be part of a mentoring program. As such, further research should be conducted to determine the influence of student’s motivation to enhance academic excellence for the students.